Influence of implant mucosal thickness on early bone loss: a systematic review with meta-analysis - Di Gianfilippo, Riccardo (J Periodontal Implant Sci, 2020)
PURPOSE: Marginal bone loss (MBL) is an important clinical issue in implant therapy. One feature that has been cited as a contributing factor to this bone loss is peri-implant mucosal thickness. Therefore, in this report, we conducted a systematic review of the literature comparing bone remodeling around implants placed in areas with thick (≥2-mm) vs. thin (<2-mm) mucosa. METHODS: A PICO question was defined. Manual and electronic searches were performed of the MEDLINE/PubMed and Cochrane Oral Health Group databases. The inclusion criteria were prospective studies that documented soft tissue thickness with direct intraoperative measurements and that included at least 1 year of follow-up. When possible, a meta-analysis was performed for both the overall and subgroup analyses. RESULTS: Thirteen papers fulfilled the inclusion criteria. A meta-analysis of 7 randomized clinical trials was conducted. Significantly less bone loss was found around implants with thick mucosa than around those with thin mucosa (difference, −0.53 mm; P<0.0001). Subgroups were analyzed regarding the apico-coronal positioning, the use of platform-matched vs. platform-switched (PS) connections, and the use of cement-retained vs. screw-retained prostheses. In these analyses, thick mucosa was found to be associated with significantly less MBL than thin mucosa (P<0.0001). Among non-matching (PS) connections and screw-retained prostheses, bone levels were not affected by mucosal thickness. CONCLUSIONS: Soft tissue thickness was found to be correlated with MBL except in cases of PS connections used on implants with thin tissues and screw-retained prostheses. Mucosal thickness did not affect implant survival or the occurrence of biological or aesthetic complications. TRIAL REGISTRATION: International Prospective Register of Systematic Reviews (PROSPERO): CRD42018084598